Vibrational and Thermal Properties of Crystalline Topiramate - Diniz Maciel de Sena JÃnior (2008)
The scientific interest on molecular crystals stems from their great versatility and ease of processing. For pharmaceutically active ingredients, the structure-activity relationship is of major importance. Topiramate, a white and crystalline solid, is a powerful drug efficiently employed to control epilepsy symptoms. The mechanism of action involves a negative modulatory effect on the AMPA/kainate subtypes of glutamate receptors and some types of voltage-gated Na+ and Ca2+ channels, and a positive modulatory effect on some types of GABAA receptors and at least one type of K+ channels in neurons. Despite its pharmacological attributes, the lack of publications regarding its physical-chemical properties in the literature is apparent. In order to fill this gap, a research comprising vibrational spectroscopy techniques (Raman and infrared), thermal analysis (TGA/DTA/DSC), and theoretical calculations, was carried out. With the aid of calculations employing density functional theory (DFT), most of the observed vibrational bands is assigned. Consideration of Raman spectra recorded at temperatures above and below room temperature, as well as under high hydrostatic pressures, indicated maintenance of the orthorhombic crystalline structure under the diverse thermodynamic conditions employed. Thermal analysis, however, showed that, after the melting point, the sample undergoes decomposition in a process comprising three stages, possibly initiated with loss of the sulfamate group by the molecule. This event inspired a theoretical study aimed at promoting the sulfamate group bond breakage in a controlled way by employing a laser instead of heat. This was accomplished by quantum dynamics simulations which showed that, by using a set of ultrashort pulses in the infrared region, it is possible to reach levels close to 70 % dissociation in less than 3 ps.